Language Acquisition Through Kitab Mabadi Fiqh in Pesantren Learning Across Traditional and Modern Eras - Islamiyah, Dhana; Nasrullah, M. Alaika (AL-FIKRA, 2025)
Arabic is an important element in pesantren education. In the context of pesantren, Arabic is the core language of learning. The yellow book such as Mabadi Fiqh is one example of a learning element that requires Arabic to understand its content. However, from time to time the learning system began to evolve with the times. This also has an impact on interest in learning Arabic which is considered an outdated language. This study aims to analyze the use of the Mabadi Fiqh book as a medium of learning Arabic at the Diniyyah Al-Amiriyah Madrasah School of Darussalam Islamic Boarding School to increase students' interest in learning Arabic and its development from the traditional and modern era. The method used in this research is a qualitative method with data collection techniques using observation, interviews, and document analysis at the madrasah diniyyah school of the Darussalam Islamic boarding school. The results showed that in the traditional era of Arabic language learning using the mabadi fiqih book in the Darussalam Islamic boarding school based on the sorogan and bandongan methods was considered effective in increasing students' understanding of Arabic but lacked student interest in deepening it. therefore the Darussalam Islamic boarding school made innovations that were adapted to the modern era in this Arabic language learning method while still maintaining the mabadi fiqih book as a learning medium. This change in learning methods has made students have a higher interest in deepening Arabic than in using traditional methods